Para uma crítica à sociedade da administração dos afetos: ou sobre quem é digno de viver no capitalismo - Castro, Emanuel Messias Aguiar de (2017)
The text presented here intends to present a critical diagnosis of the conditions of possibility of the insurgency of life forms in capitalism. In this way, we have evoked throughout the text the relation between capitalism, rationalities and ideology, in order to understand how the forms of domination and exploitation are organized by condensing themselves into the forms of life. The diagnosis, besides composing the objective of this work, is also the method used to achieve it. We’ve tried, throughout the text, to reconstruct the contingencies of capitalism (in its dimension of political economy), of rationalities and ideologies. It was not, however, a question of the reconstruction of the ways of life of the capitalism in the various phases presented here. Instead, from the hegemonic conformations of these concepts, the goal is to present how, at the macro political level, these influence on the dispositions and tendencies of the forms of sociability. The central hypothesis presented here, however, is that such provisions are imbricated in the management of motilities. Underlying the diagnostic work, a complementary diagnosis was necessary: the administration of the affections. With this, in the first part of the text, composed by the first three chapters, one perceives an effort of the forms of rationality in offering an ideal of happiness. However, by evoking psychoanalysis as a critical and analytical tool of this work, fear and anguish arise as affections with a strong power to influence the tendencies and dispositions of life forms. The literature also offered the idea of an affection that does not participate in the management circuit: the helplessness. Before this the questioning about the figures that are placed outside the forms of lives became necessary. The concept of "unworthy life" then emerged as an analytical category. Thus, in the last part of the work the relations between the affective circuits, the forms of life and the "unworthy life" were discussed. The psychoanalytic notion of jouissance was very important for this, since all the final analysis is based on the idea of the passage from a society that regulates through the prohibition to a society that regulates through the incentive. Finally, we tried to answer the question that entitles this text: "who is worth living in capitalism?".